2014
DOI: 10.4155/tde.14.86
|View full text |Cite
|
Sign up to set email alerts
|

Future of Sustained Protein Delivery

Abstract: “Despite limitations associated with every approach, delivery of proteins for an extended duration in a controlled manner is achievable… a clinically acceptable formulation that delivers proteins over a period of months is largely an unmet need.”

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The controlled release of protein into the cytosol over time is a largely unmet need that would provide for a high level of control over protein activity within the cell. 23 Recent work by Wojnilowicz et al demonstrated endosomal lysis and subsequent burst release of highly branched and rigid cationic polymers, such as dendritic glycogen, 24 while Rehman et al demonstrated burst release, but not complete endosomal rupture, with flexible linear PEI (LPEI) and passive "leaky" release with liposomes where a distinct burst event could not be identified. 22 Whether carrier architecture favors burst versus sustained release and over what time frame is crucial information that will allow protein carriers to be engineered to optimize therapeutic parameters.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The controlled release of protein into the cytosol over time is a largely unmet need that would provide for a high level of control over protein activity within the cell. 23 Recent work by Wojnilowicz et al demonstrated endosomal lysis and subsequent burst release of highly branched and rigid cationic polymers, such as dendritic glycogen, 24 while Rehman et al demonstrated burst release, but not complete endosomal rupture, with flexible linear PEI (LPEI) and passive "leaky" release with liposomes where a distinct burst event could not be identified. 22 Whether carrier architecture favors burst versus sustained release and over what time frame is crucial information that will allow protein carriers to be engineered to optimize therapeutic parameters.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There has been a substantial rise in the number of protein and peptide biologics in clinical trials for various diseases (Vaishya et al, 2014; Vaishya and Mitra, 2014). Recent advancements in protein engineering allow for rapid development of new peptide/protein therapeutics along with improved understanding of pharmacokinetics and pharmacodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…MPs are formulated with PLGA-glucose polymer for delivery over a period of 4 weeks. Lactide- and glycolide-based biodegradable polymers such as poly(D,L-lactide-coglycolide) (PLGA) and poly(D,L-lactide) (PLA) are FDA-approved and have been widely investigated for the sustained release of therapeutic peptides and proteins (Vaishya et al, 2014; Vaishya and Mitra, 2014). However, these polymers may not be suitable for delivering peptide and protein biologics as recent studies indicate that peptides/proteins are susceptible to acylation within the microenvironment of particles during release (Ghassemi et al, 2012; Ibrahim et al, 2005; Murty et al, 2003).…”
Section: Introductionmentioning
confidence: 99%